REKONSTRUKSI PEMIKIRAN TEOLOGI PROGRESIF HASSAN HANAFI SEBAGAI SOLUSI ATAS PERMASALAHAN UMAT ISLAM - Syafrial N; Ario Putra; Melani Novita Sari (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This paper examines the transformation of classical Islamic theology so that it has relevance to the situation and condition of mankind, especially Muslims today. The research method used in this research is descriptive exploratory method, descriptive research is research that aims to describe or describe clearly the problems studied. While exploratory is a method that serves to deepen intellectual treasures or to get new ideas in a research. One of the transformations in theology was carried out by Hassan Hanafi. Hassan Hanafi is an Egyptian Muslim leader. In the view initiated by Hassan Hanafi, he said it was time for theology to have a new direction that was more appropriate and in line with the times. The new direction is to change a more metaphysical (theocentric) theology to a more anthropocentric theology. According to Hassan Hanafi, anthropocentric theology can have an influence or contribution to the progress of Muslims, because Muslims are forced to be able to see and analyze human problems from a theological persepective